Developing an Applicable BalÄgah Textbook for Arabic Language Education Students at IAIN Pekalongan - Moh Nurul Huda; Rofiqotul Aini (Jurnal Alsinatuna, 2020)
This study aims to develop an applicable balÄgah textbook for the Arabic Language Education (PBA) students of IAIN Pekalongan and to find out its test validity and application. Using the Research and Development method, the study found that the majority of students want a balÄgah textbook that discusses ilm bayan (such as tasybih, majÄz, and kinÄyah) and ilm ma'ani (such as kalam khabari, kalam insya'i, qaá¹£r, faá¹£l and waá¹£l, etc.). The students also want a textbook that is brief, simple, and easy to understand. Meanwhile, the test validity from some expert validators indicated a good result with an average value of 4 points considering that the balÄgah textbook design in each theme contains a lot of text analysis exercises taken from al-Qur'an and Hadith to make the textbook more applicable. Next, the application of the balÄgah textbook may involve several methods, i.e. the jigsaw method, the discussion method (question-answer method), and the taá¹bÄ«qi method (direct practice) by analyzing the Arabic texts